SOLIDARITY ECONOMY ACTIONS IN A COOPERATIVE OF COLLECTORS IN BLUMENAU/SC - Soler, Rodrigo Diaz de Vivar y (2022)
In this paper we present the actions developed by the Projeto Economia Solidária e Sustentabilidade: gestão da produção social para o fortalecimento de uma Cooperativa dos Trabalhadores de Coletores de Resíduos Recicláveis de Blumenau. This project was coordinated by the Psychology, Production Engineering and Social Service of the Universidade Regional de Blumenau (FURB) in a cooperative of recyclable material collectors under the solidarity economy paradigm. These actions took place between the years 2020 and 2021 from activities that involved: a) the strategic advice of the cooperative, b) field visits, and c) the socioeconomic diagnosis of the cooperative members. These procedures were integrated by means of inter-disciplinary activities, whose foundation was the mediation between the executing team and the cooperative members. As it is a population in a situation of social and economic vulnerability, the relevance of extension activities such as those we carry out is in direct consonance with the principles of university extension, among which we can highlight the offer of services in conjunction with public policies necessary to improve the population's quality of life. On the other hand, the strategies developed indicate that the role of the solidarity economy is to make solidarity and community ways of strengthening bonds operate, thus contributing so that the effects of social exclusion can be minimally mitigated by income generation actions.